(untitled) (Sociologisk Forskning, 2012)
This article centres on issues of vulnerability and being compromised in feminist research where the focus has frequently been on researching the same. Compromise, here used in its pejorative sense, may for instance occur in terms of one’s research topic, the methods one utilizes, or the participants chosen for a study. Drawing on a range of examples including the methodological work of Ann Oakley (1981, 2000) as well as three articles on researching men that appeared in the journal Signs in 2005, I argue that feminist researchers, possibly because they work in an identity-based discipline, may be diversely vulnerable when researching the same and/or researching the different, and can be compromised both by how they are treated by those whom they encounter in their research and by their own behaviour in that context. I suggest that these concerns are under-articulated in feminist research and conclude with a series of questions that need to be raised.